Metastatic deaths in retinoblastoma patients treated with intraarterial chemotherapy (ophthalmic artery chemosurgery) worldwide - Abramson, David H. (Int J Retina Vitreous, 2017)
BACKGROUND: Ophthalmic artery chemosurgery [OAC, intra-arterial chemotherapy (IAC)] was introduced in 2006 as treatment modality for intraocular retinoblastoma. The purpose of this commentary is to retrospectively review the incidence of metastatic deaths in retinoblastoma patients treated with OAC worldwide over a 10 year period. Retrospective data regarding metastatic deaths was collected from six international retinoblastoma centers (New York City USA, Philadelphia USA, Sao Paulo Brazil, Siena Italy, Lausanne Switzerland and Buenos Aires Argentina). All retinoblastoma patients from these centers (naive and recurrent, unilateral and bilateral) treated with OAC/IAC since 2006 have been included in this study. Data regarding number of patients, number of OAC/IAC infusions, number unilateral and bilateral, number treated for naive disease or salvage and number of metastatic deaths have been assessed. Over a 10-year period of time 1139 patients received OAC/IAC for 4396 infusions. At last follow-up there were only three metastatic deaths (all treated in Buenos Aires). CONCLUSION: The current survey assessed the recorded risk of metastatic deaths in six retinoblastoma centers worldwide in children with retinoblastoma (unilateral or bilateral) treated with OAC/IAC as primary or secondary therapy. Overall, the observed risk for metastatic deaths from retinoblastoma was <1% in OAC/IAC treated children.